LMS-BIDAK AS A DIGITAL LEARNING INNOVATION: EXAMINING THE ROLE OF USABILITY IN ENHANCING STUDENTS’ LEARNING MOTIVATION AND CREATIVE THINKING - Otang Kurniaman; Hadriana Hadriana; Nur Islami; Zetra Hainul Putra; Eddy Noviana; Beny Al Fajar; Radini Radini (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
The integration of Learning Management Systems (LMS) in higher education has gained strategic importance, especially in the post-pandemic context. Nevertheless, empirical investigations into the effectiveness of locally developed LMS platforms such as BIDAK (Read, Identify, Discuss, Act, Conclude) in fostering university students’ learning motivation and creative thinking remain limited. This study aims to examine the impact of LMS-BIDAK usability on students’ motivation and creative thinking abilities within a higher education environment. Addressing a notable gap in the literature, the research highlights the scarcity of studies focused on the usability dimension of locally designed LMS platforms in Indonesian tertiary education. The novelty of this research lies in its contextual application of LMS-BIDAK and the use of a quantitative approach employing Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that LMS-BIDAK usability significantly influences learning motivation (t = 26.438; p = 0.000) and creative thinking (t = 75.755; p = 0.000), with R² values of 0.636 and 0.783, respectively. These findings underscore the critical role of system usability in enhancing the quality of digital learning experiences. The study implies that educational technology developers and policymakers must prioritise user-centred design to optimise student engagement and support the development of 21st-century competencies.